Effect of the current and pressure on weld strength for IBS rebar machine - Zainudin, Muhammad Faiz; Ahmad Shahir, Jamaludin; Mohamad Rusydi, Mohamad Yasin (Penerbit UMP, 2022)
The increase of population results to the increase of housing in Malaysia. One of the technologies of building houses is using the technique of prefabrication by manufacturing the walls, roof and pillars in factory and assembling the part at the construction site. This research is to study the effect of pressure and time on weld strength of IBS Rebar. In conducting the study, the data for the parameter was collected from the IBS fabrication site in Mahligai Idaman in Kota Bharu, Kelantan. The machine used spot weld to joint the concrete rebar together to make the structure of prefab. The parameter that were taken for this study are current and pressure. The result showed the effect of current and pressure to Ultimate Tensile Stress and Young Modulus. These result suggest that the effect of current and pressure significantly affect the strength of the weldment of the spot weld. On this basis, the parameter of current and pressure need to be account when run the IBS rebar machine.